Rezygnacja z katechezy szkolnej jako przejaw laicyzacji społeczeństwa - Wajs, Piotr (Społeczeństwo, 2022)
Summary: The obligation to Catholic educate their children is assumed by the spouses who enter into a sacramental marriage by the very nature of this sacrament. Each subsequent year shows, however, that the issue of participation in school catechesis for many is no longer something natural, even if the family considers itself Catholic. This article is meant to be a voice that describes the situation from the point of view of religion teachers. In the introduction, selected documents of the Church were indicated, the reasons were analyzed and proposed solutions that could reduce this trend of withdrawal from participation in school catechesis. The new General Directory on Catechesis shows the way of renewal. However, all activities will not be successful if it is not possible to build an appropriate thread of understanding with the parents, who are mostly responsible for participating or not participating in religion lessons